Silk fibroin and recombinant elastin blend nano-coatings for implantable medical devices - Joseph, Emmanuel; Kane, Kartiki; Parekh, Nimisha; Nisal, Anuya; Janorkar, V. Amol (Materials Today Communications, 2022)
Silicone breast implants are conventionally used to reconstruct the shape and size of the breast in breast cancer patients. However, rate of failure of implants due to formation of capsular contracture is significantly high. Recent studies have shown that coating the surface of the implant with a biocompatible polymer can mitigate this risk. Here, we have modified the surface of implant using a biocompatible natural biopolymer silk fibroin (SF). Further, we have developed formulations of SF with a recombinantly produced elastin-like-peptide (ELP) and compared their performance with a known anti-fouling hydrophilic polymer - polyethylene oxide (PEO). Microscopic and spectroscopic characterization confirm the formation of uniform coatings. These coatings have been also characterized for their ability to resists crack formation. Further, the coatings have been evaluated for their biological performance. Our studies show that addition of 25 wt% of ELP to SF significantly enhances the crack resistance for the coatings. In addition, SF/ELP coatings reduce the adsorption of blood plasma proteins by more than 80 %. Preliminary analysis shows that the SF/ELP blend coatings are non-cytotoxic and support adhesion, growth and proliferation of fibroblast cells. The study therefore demonstrates that SF/ELP coatings have the potential to mitigate the risk of breast implant failure.
Keywords: Blood plasma; Crack resistance; Protein adsorption; Recombinant elastin; Silk fibroin